Department Versus Division: An In-Depth Analysis of Units of Plastic Surgery and Other Surgical Specialties at Their Institutions. Issue 1 (10th January 2022) - Murphy, Alexander I.; Mellia, Joseph A.; Diatta, Fortunay; Mauch, Jaclyn T.; Asadourian, Paul A.; Christopher, Adrienne N.; Azoury, Saïd C.; Fischer, John P.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: An increasing number of plastic and reconstructive surgery (PRS) units have transitioned from divisions to departments in recent years. This study aimed to identify quantifiable differences that may reflect challenges and benefits associated with each type of unit. We conducted a cross-sectional analysis of publicly-available data on characteristics of academic medical institutions housing PRS units, faculty size of surgical units within these institutions, and academic environments of PRS units themselves. Univariate analysis compared PRS divisions versus departments. Matched-paired testing compared PRS units versus other intra-institutional surgical departments. Compared to PRS divisions (n = 64), departments (n = 22) are at institutions with more surgical departments overall ( P  = 0.0071), particularly departments that are traditionally divisions within the department of surgery (ie urology). Compared to PRS divisions, PRS departments have faculty size that more closely resembles other intra-institutional surgical departments, especially for full-time surgical faculty and faculty in areas of clinical overlap with other departments like hand surgery. Plastic and reconstructive surgery departments differ from PRS divisions by certain academic measures, including offering more clinical fellowships ( P  = 0.005), running more basic science laboratories ( P  = 0.033), supporting more nonclinical research faculty ( P  = 0.0417), and training residents who produce more publications during residency ( P  = 0.002). Institutions with PRS divisions may be less favorable environments for surgical divisions to become departments, but other recently-transitioned divisions could provide blueprints for PRS to follow suit. Bolstering full-time surgical faculty numbers and faculty in areas of clinical overlap could be useful for PRS divisions seeking departmental status. Transitioning to department may yield objective academic benefits for PRS units.